Identification of potential miRNA biomarkers for neurobrucellosis diagnosis - Liu, Meiling; Feng, Liping; Shi, Shujun; Guo, Yuzhou; Lv, Menghan; Li, Zhengyu; Wang, Xintian; Yang, Hao; Zhang, Zhelin (Frontiers in Physiology, 2025)
BackgroundNeurobrucellosis (NB) is a rare complication of brucellosis that presentis with a variety of clinical symptoms, complicating its diagnosis. This study aimed to analyze the microRNA (miRNA) profile of cerebrospinal fluid (CSF) in NB patients to identify potential biomarkers for NB diagnosis.MethodsSmall RNA sequencing was utilized to identify differential expressed miRNAs (DEmiRNAs) in CSF samples from both control and NB patients (in-house cohort). The GSE107554 dataset (validation cohort) from the GEO database was used to validate the expression levels of these DEmiRNAs. Subsequently, LASSO regression analysis was conducted to construct a diagnostic risk score model based on common miRNAs identified in both the in-house and validation cohorts.ResultsThe study identified 51 DEmiRNAs between the control and NB groups, based on the data from the in-house cohort. Among these, four common miRNAs (miR-342-3p, miR-576-5p, miR-15b-5p and miR-499a-5p) were significantly elevated in the infection group compared to controls in both the in-house and validation cohorts. Subsequently, a novel NB diagnostic signature comprising two miRNAs (miR-576-5p and miR-499a-5p) was developed using the LASSO regression analysis. Receiver operating characteristic (ROC) analysis demonstrated the good diagnostic potential of this miRNA signature in both cohorts. RT-qPCR analysis indicated elevated levels of miR-576-5p and miR-499a-5p in CSF samples of NB patients compared to controls. Additionally, RT-qPCR results revealed decreased levels of VAV3 (vav guanine nucleotide exchange factor 3, a target of miR-499a-5p) and IGF1 (insulin like growth factor 1, a target of miR-576-5p) in the CSF samples of NB patients.ConclusionCollectively, miR-576-5p and miR-499a-5p may serve as potential biomarkers for the diagnosis of NB.